Arabidopsis thaliana siRNA biogenesis mutants have the lower frequency of homologous recombination. (2nd July 2016) - Yao, Youli; Bilichak, Andriy; Golubov, Andrey; Kovalchuk, Igor
ABSTRACT: Small interfering RNAs (siRNAs) are involved in the regulation of plant development and response to stress. We have previously shown that mutants impaired in Dicer-like 2 ( DCL2 ), DCL3 and DCL4, RDR2, RDR6 and NPRD1 are partially impaired in their response to stress and dcl2 and dcl3 plants are also impaired in transgenerational response to stress, including changes in homologous recombination frequency (HRF). Here, we have analyzed genome stability of dcl2, dcl3, dcl4, dcl2 dcl3, dcl2 dcl3 dcl4 and rdr6 mutants by measuring the non-induced and the stress-induced recombination frequency. We found that all mutants had the lower spontaneous HRF. The analysis of strand breaks showed that all tested Arabidopsis mutants had a higher level of spontaneous strand breaks, suggesting that the lower HRF is not due to the unusually low level of breaks. Exposure to methyl methane sulfonate (MMS) resulted in an increase in the level of strand breaks in wild-type plants and a decrease in mutants. All mutants had the higher methylation of cytosines at CpG sites under non-induced conditions. Exposure to MMS resulted in a decrease in methylation level in wild-type plants and an increase in methylation in all dcl mutants. The expression of several DNA repair genes was altered in dcl4 plants under non-induced and induced conditions. Our data suggest that siRNA biogenesis may be essential for the maintenance of the genome stability and stress response in Arabidopsis.